Macro-economic determinant and interdependence of the stock markets - Asim Rafiq; Shahbib Hassan (Economic Journal of Emerging Markets, 2019)
This study examines the time-varying long-term stock market interdependence between china and the ten emerging economies, using Johansen co-integration and Dynamic Conditional Correlation-Generalized Autoregressive Conditional Heteroskedasticity (DCC GARCH) model. It analyses the dynamic association between the equity markets and the macroeconomic determinants using panel regression analysis. Findings/originality: The results indicate that the Chinese stock market are co-integrated with the stock market of the other emerging markets. It confirms that the relationship between china and the other emerging economies has been increasing over time. It concludes that there is long run interdependence between the Chinese and the other emerging economies. In addition, the results of the panel regression show that macroeconomic determinants have no significant effect on the equity market correlations between China and the ten emerging economies.